Comparison of secondary prevention in coronary heart disease patients living in rural and urban areas - Salih Kılıç; Erhan Saraçoğlu; Yusuf Çekici; Arafat Yıldırım; Zülfiye Kuzu; Dilara Deniz Kılıç; Meral Kayıkçıoglu (KARE Publishing, 2019)
Objective: The aim of the present study was to assess differences between urban and rural patients with coronary heart disease (CHD) with respect to secondary prevention. Methods: This cross-sectional study included all consecutive patients diagnosed with CHD at 2 cardiology clinics between January 2016 and January 2017. The demographic characteristics and laboratory parameters were recorded at routine control visits. The patients were divided into 2 groups according to residence based on their statements: urban (n=1752) and rural (n=456). Results: The median age of the patients was 64 years (interquartile range: 12 years). A mean of 4.1+-2.1 years had passed after the first (index) coronary event. It was determined that 22.2% of the patients continued to smoke. The rate of quitting was significantly higher in the urban group (20.5% vs. 11.2%; p<0.001). The presence of hypertension (64.3% vs. 56.7%), diabetes mellitus (45.6% vs. 39.2%), cerebrovascular events (9.2% vs. 3.8%), and chronic obstructive pulmonary disease (11.4% vs. 5.5%) was significantly greater among the rural patients (p<0.05 for each). In all, 34.2% were obese, and the number of obese patients was significantly greater among the rural patients (46.4% vs. 31.2%; p<0.001). The number of patients performing regular exercise was significantly lower in the rural patient group (34.4% vs. 23.9%; p<0.001). Overall, 88.9% of the patients were taking antiplatelet agents, 62.1% were taking statins, 73.1% were taking beta-blockers, and 34.2% were taking ACEI/ARB. The rate of medication use was significantly greater among urban patients compared with rural patients (p<0.05 in all cases). Conclusion: Secondary prevention efforts among patients with CHD require additional improvement. Moreover, secondary prevention is currently less successful among the rural population than the urban population.